Lviv period for Smoluchowski: Science, teaching, and beyond - Rovenchak, A. (Condensed Matter Physics, 2012)
A major part of Marian Smoluchowski's achievements in science corresponds to the period of his work at the University of Lviv. Since this part is well described in the literature, in the paper the emphasis is made on some less known activities of this outstanding scientist: his teaching, his organizational efforts, and even his hobbies. The list of publications corresponding to the Lviv period is given. iльшiсть наукових досягнень Марiана Смолуховського припадає на час його роботи у Львiвському унiверситетi. Оскiльки ця сторона дiяльностi вченого добре описана в лiтературi, то у статтi зроблено наголос на менш вiдомих напрямках роботи цього видатного вченого: викладання й орґанiзацiйнi заходи i навiть його хобi. Наведено також перелiк публiкацiй львiвського перiоду.